Podcast videos-based language learning materials integrated with metacognitive skills in improving EFL learners’ speaking skills and intercultural pragmatic competences - Mahyun Ismail; Haerazi Haerazi; Lalu Ari Irawan (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
Recognizing that speaking proficiency requires not only linguistic accuracy but also metacognitive awareness and intercultural sensitivity, the research introduces podcast videos as authentic resources to provide contextual exposure to real-life communication. This study investigates the effectiveness of podcast video–based instructional materials integrated with metacognitive strategies in enhancing English as a Foreign Language (EFL) learners’ speaking skills and intercultural pragmatic competence. Employing a mixed-method concurrent embedded design, the study involved 67 middle school students in Central Lombok, Indonesia, who were divided into experimental and control groups. Data were collected through pretests, posttests, and interviews, with instruments designed to measure speaking performance, intercultural pragmatic competence, and metacognitive skills. Quantitative results revealed significant improvements in the experimental group’s speaking and intercultural competence, supported by high mean scores and statistically significant differences in t-test analyses. Metacognitive integration also fostered learners’ ability to plan, monitor, and evaluate their communication strategies, leading to greater learner autonomy. Qualitative findings indicated positive learner perceptions, with students highlighting the authenticity, motivation, and relevance of the podcast-based materials. Podcast videos mixed with metacognitive scaffolding appear to be a unique and effective EFL teaching method. The study offers both theoretical and practical implications for technology-enhanced, student-centered pedagogy.